Analisis Penerapan Sistem Pengendalian Manajemen untuk Meningkatkan Kinerja Perusahaan pada PT. Melu Bangun Wiweka - Sarah Simanjuntak; Dina Oviani Siregar; Enjelina Jurela Rotua Lumban Tobing; Toman Sony Tambunan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the implementation of management control systems in improving company performance at PT. Melu Bangun Wiweka (MBW), a private construction company facing tight competition in the construction services industry. The study uses a qualitative approach with a descriptive method, where data is obtained through interviews with the company. The results of the study indicate that PT. MBW has implemented a fairly good management control system through the stages of strategic planning, budgeting, activity implementation, and performance evaluation. This system has been proven to play an important role in directing organizational activities and improving employee performance through the provision of rewards and sanctions based on standard operating procedures. This study concludes that a structured and communicative management control system can improve the effectiveness and efficiency of the company in achieving its goals. It is recommended that the company continue to improve employee understanding of the company's vision and strengthen the evaluation system to face competitive challenges in the future